Gambaran Dukungan Keluarga Terhadap Kecemasan pada Ibu Hamil di Wilayah Kerja Puskesmas Bajeng - Sri Wahyuni R; Didin Wahyudi; Sartika Sartika (Fatiakara Care: Jurnal Ilmiah Keperawatan, 2025)
Pregnancy is a period when the body of a pregnant woman experiences physical and psychological changes due to an increase in pregnancy hormones. Hormonal changes experienced by pregnant women cause emotional changes and bring up several reactions such as happy, sensitive, easily sad, disappointed, offended, anxious and even stressed. With these conditions, family support is needed during pregnancy and is very important for pregnant women. The purpose of this study was to determine family support for anxiety in pregnant women in the working area of the bajeng health center in Bajeng District, Gowa Regency. The type of research used in this study is a quantitative descriptive study in which this study describes family support for anxiety in pregnant women. The results of this study regarding the Overview of Family Support for Anxiety in Pregnant Women at the Bajeng Health Center, show that of the 35 respondents obtained emotional support support (85.7%), it is hoped that further researchers can use the results of this study as material and data sources to carry out research on family support for anxiety in pregnant women.